Pemantauan Penggunaan Listrik Peralatan Rumah Tangga Melalui Telepon Genggam Pengguna - Farid Ishartomo; Andi Dharmawan (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2011)
Many people, either intentional orunintentional, did not know they left their electricalhome appliances such as air conditioners, televisions,lights, etc. still in an active state when leaving theirhomes, so we need a system that can wirelesslymonitor the electricity usage in their homes. In thisstudy, it has been designed a system that can monitorthe use of electrical equipment which used in thehome. This system utilize the internet via mobilephone technology to monitor electric power usage athome and control their use by user’s mobile phone. Toprocess the data output from current and voltagesensor which used to measure the values of electriccurrent and voltage, it use AT Mega 128Microcontroller with 10-bit ADC inside. The results ofthis study is a package of both hardware and softwarefor mobile phones and for home monitoring server.